Review on Dye Removal from Its Aqueous Solution into Alternative Cost Effective and Non-Conventional Adsorbents - Dawood, Sara.; Sen, Tushar (JScholar Publishers, 2014)
Dyes are complex organic compounds which are used by various industries to colour their products. These dyes are purged from various industrial sources such as textile, cosmetic, paper, leather, rubber and printing industries. Wastewater effluents contain dyes which may cause potential hazards to the environment. Some of these dyes are toxic, carcinogenic and can cause skin and eye irritation. Therefore, many researchers have been studied the effectiveness of dyes removal from aqueous solution by different separation methods. Different separation techniques have been used for the treatment of dye-bearing wastewater such as adsorption, coagulation/flocculation, advanced oxidation technologies, ozonation, and membrane-filtration, aerobic and anaerobic degradation. All dye separation techniques have their own limitation in terms of design, operation efficiency and total cost. This review paper provides extensive literature information about dyes, its classification and toxicity together with various treatment methods into dye adsorption characteristics of several non-conventional cost effective sustainable adsorbents. The mechanism and the effects of various physio-chemical process parameters on dye adsorption are presented here.